KANDUNGAN GIZI DAN KARAKTERISTIK MI BASAH DENGAN SUBTITUSI DAGING KEONG MAS (Pomacea canaliculata) - Agus Mualim; Susi Lestari; Siti Hanggita R.J (Universitas Sriwijaya, 2013)
The purpose of this research was to determine nutrient contents and characteristics of wet noodles which substituted with meat of Golden Snail (Pomacea Canaliculata). The nonfactorial complete randomized design was used with five treatments and 3 replications. The different concentration meat of golden snail A0 (0%), A1 (10%), A2 (20%), A3 (30%), A4 (40%).The parameters were proximate analysis (water content, ash content, fat content, protein content and carbohydrate content), colour test, elasticity test, sensory (color, aroma, texture, and taste). The addition meat ofgolden snail was significant on moisture content, ash content, fat content, protein content, carbohydrate content, and the color of wet noodles but was not significant on elasticity of wet noodles. Hedonictest was significant on the color with the addition of a wet noodle meat of golden snailand was not significant on aroma, texture and taste of wet noodles by addition meat of golden snail. Treatment A2(meat 20% and wheat 80%) was the best treatment in this research with a value of protein content 15.57%, carbohydrate content 8.4%, fat content of2.55%, moisture content 56.99% and ash content of 1.81%.